Prospective, Multicenter, Randomized, Controlled Pilot Trial of Peritoneal Hypothermia in Patients With ST-Segment—Elevation Myocardial Infarction. (March 2015) - Nichol, Graham; Strickland, Warren; Shavelle, David; Maehara, Akiko; Ben-Yehuda, Ori; Genereux, Philippe; Dressler, Ovidiu; Parvataneni, Rupa; Nichols, Melissa; McPherson, John; Barbeau, Gérald; Laddu, Abhay; et al.
<x xml:space="preserve">Abstract</x> Background— Systemic hypothermia may reduce infarct size if established before reperfusion. The large surface area of the bowel may facilitate rapid hypothermia. We therefore examined the feasibility, safety, and efficacy of hypothermia induced by an automated peritoneal lavage system in patients with ST-segment–elevation myocardial infarction undergoing primary percutaneous coronary intervention. Methods and Results— Patients with ST-segment–elevation myocardial infarction within 6 hours of symptom onset were randomized to peritoneal hypothermia before and for 3 hours after percutaneous coronary intervention versus control. The primary safety end point was the 30-day composite rate of death, reinfarction, ischemia-driven target vessel revascularization, major bleeding, sepsis, pneumonia, peritonitis, severe arrhythmia, or renal failure. The primary efficacy end point was infarct size assessed by cardiac MRI on day 3 to 5. Fifty-four patients were randomized at 7 centers to hypothermia (n=28) versus control (n=26). Hypothermia was successfully initiated in 96.3% of patients, and median [interquartile range] temperature at first balloon inflation was 34.7 [34.0–34.9]°C. Median door-to-balloon times in the hypothermia and control groups were 62 [51–81] and 47 [37–55] minutes, respectively (P=0.007). The primary safety end point occurred in 6 (21.4%) and 0 (0%) patients in the hypothermia and control groups, respectively (P=0.01), including 3 versus 0 stent thrombosis events. Infarct size was 17.2% [15.1–20.6] and 16.1% [10.0–22.2] in the hypothermia and control groups, respectively (P=0.54). Conclusions— Peritoneal hypothermia is feasible and achieves rapid cooling with only a modest increase in treatment times in the setting of ST-segment–elevation myocardial infarction. However, in the present randomized trial, peritoneal hypothermia was associated with an increased rate of adverse events without reducing infarct size. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01655433.